Study on the Effect of Salt Stress on Yield and Grain Quality Among Different Rice Varieties - Zhang, Rui; Wang, Yang; Hussain, Shahid; Yang, Shuo; Li, Rongkai; Liu, Shuli; Chen, Yinglong; Wei, Huanhe; Dai, Qigen; Hou, Hongyan (Frontiers in Plant Science, 2022)
Salt is one of the main factors limiting the use of mudflats. In this study, the yield, quality and mineral content of seeds of rice under salt stress were investigated. A pot experiment was conducted with Yangyugeng2, Xudao9 and Huageng5 under 0, 17.1, 25.6, and 34.2 mM NaCl of salt concentration treatments. The results showed that salt stress can significantly decrease panicle number, grain number per panicle, 1000-grain weight and yield of rice, and panicle number was the main cause of yield loss under saline conditions. When the salt concentration was less than 34.2 mM NaCl, salt stress increases the brown rice rate and milled rice rate of rice, and significant increases head milled rice rate of salt-sensitive varieties but decreases in salt-tolerant varieties. In addition, the grain length is more sensitive than grain width to salt stress. This study also indicates that different varieties of rice exhibit different salt tolerance under salt stress, the three rice varieties in this study, in order of salt tolerance, were Xudao9, Huageng5 and Yangyugeng2. Salt stress will increase the appearance, viscosity, degree of balance, and taste value and decrease the hardness of rice when salt concentration less than 17.1 mM NaCl in Yangyugeng2 and Huageng5 or 25.6 mM NaCl in Xudao9. The differences in starch pasting properties among rice varieties in this study were larger than the differences caused by salt stress. The uptake capacity of K, Mg, P, S and Cu ions in the seeds of different rice varieties was significantly different, and salt stress causes significant differences in the uptake capacity of K, Na, and Cu in rice seeds. Rice varieties with high salt tolerance can be selected for the development and utilization of mudflats, and low concentration of salt stress will increase the rice quality of rice, these findings are meaningful in agricultural production.